The Principle of Justice In The Revocation of Child Adoption Determination By Adoptive Parents (Study of Supreme Court Decision No. 31/Pdt.G/2022/PN Njk) - Fitria, Anugrah; Winanti, Atik (Dinasti Research, 2025)
This research examines the revocation of a child's adoption order by highlighting aspects of justice, both for the child and the adoptive parents. The focus of the discussion is directed at the Nganjuk State Court Decision No. 31/Pdt.G/2022/PN.NJK, in which the judge granted the revocation of adoption on the basis of the best interests of the child. However, the decision raises issues because it does not pay attention to the rights and contributions of adoptive parents who have provided care for many years. The type of research used is Normative Juridical with a case approach, legislation, and comparison. Data sources come from primary legal materials in the form of laws and decisions, and are strengthened by literature as secondary legal materials. Analysis is carried out qualitatively through the study of doctrine and legal norms. The results of this study indicate that the judge's consideration is more in favor of child protection, but creates an imbalance for adoptive parents. Therefore, clearer legal arrangements are needed regarding the mechanism for revocation of adoption, so as to provide legal certainty as well as a sense of justice for all parties.